Teachers' Efforts in Overcoming Difficulties Learning to Read in Elementary School Students - Kosilah Kosilah; Suarti Suarti; Manan Manan; Fani Aljaber (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to explain teachers' efforts in overcoming reading learning difficulties in grade II students of Gonda State Elementary School, Baubau City. This type of research is qualitative research with descriptive methods. The study subjects used were grade II teachers, with 23 students consisting of 11 female and 12 male students. The method or technique of data collection used is observation, interview, and documentation. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. The research results on teachers' efforts in overcoming reading learning difficulties in grade II students of Gonda State Elementary School in Baubaubau City have two steps: choosing and implementing effective learning strategies and learning methods. The learning strategy used is introducing the alphabet to students first, Utilizing reading corners, conducting tutoring, and habituating to reading together during the learning process. The learning method is by approaching students and giving reading practice tasks and giving interesting reading spelling books. The forms of teacher efforts are expected to effectively overcome students' reading learning difficulties, especially in grade II students of Gonda State Elementary School in Baubau City.